Primitive neuroectodermal tumor of the kidney: A rare case report - Talwar, Amrita (J Lab Physicians, 2018)
Renal primitive neuroectodermal tumor (PNET) is a rare primary renal neoplasm. Morphologically, it may mimic small blue round-cell tumor. Hence, histopathology in conjunction with immunohistochemistry plays a significant role in correctly diagnosing this malignancy. We report a case of PNET of kidney in a 30-year-old female with an extension to inferior vena cava, who succumbed following an aggressive course of illness.